PEDAGOGICAL PARTNERSHIP IN AN ONLINE LEARNING ENVIRONMENT DURING COVID-19 - AZZIRA, ABAS (Universiti Malaysia Sarawak (UNIMAS), 2021)
Pedagogical partnership refers to a curriculum formed together with various internal and external partners such as communities, industries, research institutes as well as students. This study focuses on the partnership with students, also known as student- as-a-friend, faculty-student or students-staff partnership. Most existing pedagogical partnership programmes focus on physical classroom learning. Since the outbreak of COVID-19, educational institutions around the world have decided to use the available technical resources to produce online learning materials for students from all academic fields. So, this study was conducted as not much is examined on how pedagogical partnership can inform online pedagogical practices to bring about a fairer and more inclusive learning environment. Focusing on a chosen online course, this study also reflected on appropriate strategies to improve students’ online learning experiences in that particular course. This study employed both qualitative and quantitative data. The findings show both positive and negative learning behaviour plus learning experiences encountered by students. This study also shows the importance of a sense of presence and community, reliable technology, and students’ personalities. The case study also offers valuable information on the role as a student partner in the partnership plus challenges faced. It also provides some research ideas and suggestions to obtain a deeper understanding of this pedagogical partnership approach.